Pengaruh Kepemimpinan Kepala Sekolah, Motivasi Kerja, dan Kepuasan Kerja terhadap Kinerja Guru SMA Mitra Kerja Eduversal se-Indonesia - Eko Andi Hartono; Supriyoko (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to analyze the influence of the principal's leadership, work motivation, and job satisfaction simultaneously and partially on the performance of SMA Mitra Eduversal High School teachers throughout Indonesia. This research was conducted in 8 SMA Partners Eduversal in Indonesia. This research is quantitative research. The population of this research is all teachers in 8 SMA Mitra Kerja Eduversal in Indonesia totaling 387 teachers. The sample was used with the Slovin formula and 197 samples of teachers were obtained. Validity test using product moment correlation and reliability test using Cronbach's Alpha. Test requirements analysis using normality test, linearity test, and multicollinearity test. Hypothesis testing using multiple regression analysis. The results of this study were obtained together that the principal's leadership, work motivation and job satisfaction had a very significant positive influence. While partially, both principal leadership, work motivation and job satisfaction have a positive and significant influence on teacher performance. This study also found that the effective contribution of the principal's leadership, work motivation and job satisfaction together on teacher performance was 22.8%. The variable of work motivation has the greatest influence.